2012
DOI: 10.4028/www.scientific.net/amr.626.121
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Engineered Cementitious Composite with Palm Oil Fuel Ash as a Supplementary Binder

Abstract: Palm oil fuel ash (POFA) was used to produce engineered cementitious composite (ECC) in this research where ECC mixtures containing different volume of POFA (up to 55% by weight) of cement, were prepared. Mechanical properties of the resulting ECC mixtures were assessed using the compression, flexural and uniaxial tensile tests. The findings of the study show that the use of POFA improves the mechanical properties of the ECCs. The ECC mix with 1.2 POFA/cement ratio achieved a compressive strength of 30 MPa at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Both figures show an amorphous hump (as indicated in the circle) in the XRD pattern which indicates the presence of amorphous silica in both POFA and RHA. Previous studies have reported that the amorphous silica has an important role in the pozzolanic activity [5,9,10,11]. Meanwhile, the peak illustrated in the figures indicates the presence of crystalline in the binder.…”
Section: X-ray Diffractionmentioning
confidence: 84%
See 2 more Smart Citations
“…Both figures show an amorphous hump (as indicated in the circle) in the XRD pattern which indicates the presence of amorphous silica in both POFA and RHA. Previous studies have reported that the amorphous silica has an important role in the pozzolanic activity [5,9,10,11]. Meanwhile, the peak illustrated in the figures indicates the presence of crystalline in the binder.…”
Section: X-ray Diffractionmentioning
confidence: 84%
“…Meanwhile, the peak illustrated in the figures indicates the presence of crystalline in the binder. They only act as void filler and do not participate in the pozzolanic activity [5,9,10,11].…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…POFA has a pozzolanic properties therefore can be used as partial cement replacement without sacrificing for either the mechanical or physical properties of cement [4,7,8]. The only feasible solution to reduce future environmental problems that may be caused by disposal of POFA is to use it as replacement of cement in concrete or quartz in ceramic industry [9]. Malaysia is among the largest producers of palm oil, thus, facing environmental problems by disposing palm oil fuel ash.…”
Section: Introductionmentioning
confidence: 99%
“…POFA is a by-product from biomass thermal power plants where oil palm residues are burned to generate electricity. Malaysia is one of the largest producers of palm oil with around 41% of the total world supply in years 2009 -2010 [1][2][3][4]. In Thailand, for example, it has been estimated that 2.1 million tons of biomass was used as fuel in 2004, producing about 100,000 tons (5%) of biomass ash [5][6].…”
Section: Introductionmentioning
confidence: 99%